Spinal Cord Changes After Laminoplasty in Cervical Compressive Myelopathy: A Diffusion Tensor Imaging Study - Yang, Young-Mi; Yoo, Woo-Kyoung; Bashir, Shahid; Oh, Jae-Keun; Kwak, Yoon-Hae; Kim, Seok Woo (Frontiers in Neurology, 2018)
Purpose: Validation of the efficacy of decompression surgery in patients with cervical myelopathy (CM) is important in terms of the recovery of the integrity of the spinal cord. However, to date, no longitudinal study has addressed the underlying pathological changes using diffusion tensor imaging (DTI) in CM patients. This study aimed to determine the diffusion metrics at the lesion as well as below the lesion level longitudinally in CM patients following laminoplasty using DTI. Methods: Twenty CM patients were analyzed and compared with twenty age-matched healthy controls. The primary outcome measure was the changes in the diffusion metrics (fractional isotropy [FA], mean diffusivity [MD], axial diffusivity [AD], and radial diffusivity [RD]). The secondary outcome measure was the changes in the modified Japanese Orthopedic Association (mJOA) score. Diffusion metrics obtained from six region-of-interests (ROIs; 2 anterior, 2 posterior, 2 lateral) at the lesion and below the lesion level (C7/T1) in preoperative and 6-month postoperative conditions were compared longitudinally. Results: The CM patients showed significant changes in their postoperative diffusion metrics for the anterior ROIs compared with the preoperative measures both at and below the lesion level. In the lateral and posterior cord, the preoperative AD value decreased after laminoplasty to the control at the lesion level. In contrast, MD and RD values at the lesion level and FA value at below the lesion level remained unchanged postoperatively. In addition, the postoperative anterior FA value was positively correlated with the postoperative mJOA score below the lesion level. Conclusion: This would be the first study showing changes in the spinal cord at the lesion as well as below the lesion level after laminoplasty in CM patients, which may be associated with functional recovery.